Är kvinnor nyckeln till ett hållbart företagande? - Snoei,Iris; Lindahl,Sofia; Källberg,Evelinn (2022)
Title: Are women the key to sustainable business? Seminar date: 2022-06-03 Course: FEKH69, Degree Project in Accountancy, Bachelor level, 15 credits Authors: Evelinn Källberg, Sofia Lindahl, Iris Snoei Advisor: Maria Gårdängen Key words: Sustainability reporting, CSR, percentage of female board directors, board diversity Research Question: Is there a relationship between the percentage of female board directors and the quality of sustainability reporting in Swedish listed firms? Purpose: The purpose of this study is to examine whether there is a relationship between the percentage of female board directors and the quality of the sustainability reporting in Swedish listed firms. Method: The study uses a quantitative method with a deductive approach. Secondary data from annual reports and sustainability reports have been collected and analysed with the help of multiple linear regression analysis in order to examine the connection between GRI-points and percentage of female board directors. Theoretical Perspectives: This study has its foundation in previous research regarding the relationship between percentage of female board directors and sustainability reporting. In addition to this, the stakeholder theory and the resource dependence theory is used. Empirical Foundation: The empirical foundation of the study is based on 109 companies, which al have been listed on Nasdaq OMX Stockholm year 2020. Data has been collected from Retriever Business, Dagens Industri, annual reports and sustainability reports. Conclusions: The study does not find any significant relationship between the percentage of female board directors and the quality of sustainability reporting.
Keywords: Hållbarhetsrapportering; CSR; andel kvinnliga styrelseledamöter; diversitet i styrelsen; GRI